Reflections on the antinomies of Educational Inspection in Spain. An unresolved problem - Esteban Frades, Santiago (Avances en Supervisión Educativa, 2007)
The Education Inspectorate has historically suffered stages of inadequate definition which have led to several contradictions, the most important of which are the following ones: a twofold organization -High Education Inspectorate and Education Inspectorate-, the official dependence -an Administration body of civil servants or a Teaching body of civil servants-, an internal organization based on specific educational levels or a multi-level one-, semi-professional or professional enrolment, duties of control vs. advisory duties, pedagogical leadership or bureaucratic performance, and finally lack of definition, conflict and ambiguous duties. Probably due to a minor influence of political ideologies, some other Inspectorates have succeeded in undertaking a transformation from the non-democratic model of the 1960s to a model in accordance with the Spanish Constitution, which conceives supervision as integrated in the whole institutional system, under the Spanish Constitution.